2016
DOI: 10.3892/etm.2016.3712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical treatment of malignant hyperthermia in three cases

Abstract: Malignant hyperthermia (MH) is a rare life threatening inherited disorder that is triggered by drugs used for general anesthesia in susceptible persons. The symptoms include rapid increase of body temperature and severe muscle contractions. The present study includes 3 cases of MH and highlights the timely identification of symptoms for rescuing the patient. In case I, a 7-year-old male child underwent surgery with ketamine at a dose of 250 mg. After 4 h of operation, the child went through convulsions, high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…In some cases, dantrolene was administered immediately after the MH crisis triggering, both during the intraoperative [ 4 , 13 , 40 , 49 , 50 ] and postoperative [ 32 , 51 , 52 ] periods and all patients were discharged from the hospital in stable conditions. Late addition of dantrolene is also reported in intra- and postoperative MH cases with different results, and some were fatal, while others had no additional complications [ 2 , 45 , 53 , 54 ]. On the other hand, there were related intra- [ 28 , 55 ] and postoperative [ 54 ] MH cases in which dantrolene was not administrated due to non-availability of the drug in the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, dantrolene was administered immediately after the MH crisis triggering, both during the intraoperative [ 4 , 13 , 40 , 49 , 50 ] and postoperative [ 32 , 51 , 52 ] periods and all patients were discharged from the hospital in stable conditions. Late addition of dantrolene is also reported in intra- and postoperative MH cases with different results, and some were fatal, while others had no additional complications [ 2 , 45 , 53 , 54 ]. On the other hand, there were related intra- [ 28 , 55 ] and postoperative [ 54 ] MH cases in which dantrolene was not administrated due to non-availability of the drug in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Late addition of dantrolene is also reported in intra- and postoperative MH cases with different results, and some were fatal, while others had no additional complications [ 2 , 45 , 53 , 54 ]. On the other hand, there were related intra- [ 28 , 55 ] and postoperative [ 54 ] MH cases in which dantrolene was not administrated due to non-availability of the drug in the hospital. Iqbal et al (2017) [ 28 ] reported the clinical signs and laboratory parameters altered by the MH crisis were reversed with internal (ice cold saline intravenously) and external (ice packs and cold towels over the body) cooling, and the patient had full recovery before being discharged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por ser uma desordem genética do músculo esquelético, implica na diminuição da recaptação de cálcio e na liberação descontrolada do mesmo. A síndrome ocorre em pacientes susceptíveis à exposição dos agentes desencadeantes utilizados para induzir a anestesia geral [12][13][14][15] .…”
Section: Métodounclassified